Dare's Formula Specifications in Assessing Fetal Weight - Lusiana Lusia Sirait; Riwalsen Purba (poltekkes kemenkes mataram, 2021)
One of the causes of complicating labor is the fetal factor, namely the fetus's size. If it is not treated immediately, it will increase maternal and neonatal mortality rates. Accurate estimation of fetal birth weight in pregnancy and delivery is an important indicator in determining fetal well-being. Birth weight is important to measure before labor starts, which helps anticipate possible complications in pregnancy, childbirth, and the puerperium. The accuracy of estimation of fetal body weight either by measuring the fundal height or other means will affect labor management. One way to predict the estimated fetal weight, including the Dare's Formula method, is to measure the circumference of the mother's abdomen (abdominal girth) in centimeters, the measurement results times the Fundus Uterine Height (TFU) in centimeters, and the modified Niswander formula (1.12 TFU). - 7,7) 100 (gr). The design used in this study is a Quasi Experiment. Assessment The estimated fetal weight obtained from the measurement is then compared with the newborn's body weight (actual body weight). The population in this study were all pregnant women, both primiparous and multiparous. While the sample to be taken must meet the inclusion criteria that have been set. The results of the study were based on statistical tests using independent t-test, it was found that the p value (0.000) <α (0.05) means that there is a significant difference between the difference in body weight of babies born with Dare's formula and the difference in body weight of babies born with Niswander's modification, the estimated fetal weight is more. Effective using Dare's formula rather than Niswander modification.